2018
DOI: 10.1007/s12928-018-0534-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug-coated balloon angioplasty for de novo small vessel disease including chronic total occlusion and bifurcation in real-world clinical practice

Abstract: The aim of this study is to validate the efficacy of drug-coated balloons (DCBs) for real-world de novo small vessel diseases including chronic total occlusion and bifurcation. DCB angioplasty has been reported to be effective in the treatment of de novo small vessel disease. However, the number of reports that have focused on complex lesions is limited. This observational study comprised consecutive patients who underwent DCB angioplasty for de novo small vessel disease with a reference diameter of less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…All these factors together resulted in better vascular remodeling and then less lumen loss diameter and greater lumen enlargement in the DCB group. 3436 On the other hand, there were no significant differences in the incidence of target lesion revascularization, myocardial infarction, and cardiac death between the two groups during follow-up, also suggesting that DCB is non-inferior to DES in long-term outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…All these factors together resulted in better vascular remodeling and then less lumen loss diameter and greater lumen enlargement in the DCB group. 3436 On the other hand, there were no significant differences in the incidence of target lesion revascularization, myocardial infarction, and cardiac death between the two groups during follow-up, also suggesting that DCB is non-inferior to DES in long-term outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…Meanwhile evidence regarding the use of DCB in treating small vessels and bifurcation lesions is accumulating (11). Previous studies have demonstrated that the DCB-only strategy for CTO is a feasible and well-tolerated approach (12,13). We aimed to investigate the impact of long-term angiographic and clinical outcomes of DCB treatment (DCB alone or combined with DES) in de novo CTO lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of small vessel disease, DCB is also demonstrably safe and effective, and increasing evidence supports DCB in treating acute myocardial infarction (MI), bifurcation lesions, and large vessel disease (11). However, only a few studies with a small sample size and short follow-up duration have evaluated DCB in treating de novo CTO lesions (12)(13)(14). We aimed to compare the efficacy and safety of less DES strategy (DCB-only or combined with DES) and DES-only strategy in treating de novo CTO lesions in a prospective, multicenter, observational study with long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…This expanded LLL is related to the confined capability of the small vessel to address to even small neointimal proliferation after stent implantation. Diabetes mellitus is also a strong predictor of awful consequences after PCI and there is a well-documented link amongst small vessel coronary disease and this condition [14][15][16]. Drug-coating balloons (DCB) have been superior as a manner to skip the troubles seen with DES, and there is now evidence to indicate they may be a probable opportunity for treating small vessel disease [17].…”
Section: Introductionmentioning
confidence: 99%